Biochemical assessment of adequate levothyroxine replacement in primary hypothyroidism differs with different TSH assays: potential clinical implications. Issue 6 (14th May 2021) - Kalaria, Tejas R; Sanders, Anna; Ford, Clare; Buch, Harit; Fenn, Jonathan Samuel; Ashby, Helen L; Mohammed, Pervaz; Gama, Rousseau Mariano
Abstract : Aim: Thyroid stimulating hormone (TSH) assays provided by Abbott Laboratories and Roche Diagnostics are used by approximately 75% of laboratories in the UK. We assessed the potential impact of Abbott and Roche TSH assay differences on the biochemical assessment of levothyroxine replacement in primary hypothyroidism. Method: Samples from 100 consecutive primary care patients (83 women, median age 64 years, IQR 51–73 years) with primary hypothyroidism on adequate levothyroxine based on an Abbott Architect TSH in the reference range were analysed for TSH on Roche cobas within 24 hours. The Abbott and Roche TSH results were compared. Over 1 year, TSH results from patients in primary care from the laboratories with Abbott and Roche methods were compared. Results: The median (IQR) Roche TSH (2.5 (1.3–3.6) mIU/L) was 30%±10% higher (p<0.001) than Abbott TSH (1.9 (1.1–2.6) mIU/L). Although all Abbott TSH results were in the Abbott specific reference range, 14 patients (14%) had Roche TSH results above the Roche specific reference range. In the 1 year gather, Roche TSH (1.9 (1.3–2.9) mIU/L, n=103 932) results were higher (p<0.001) than Abbott TSH (1.5 (1.0–2.2) mIU/L, n=1 10 544) results. The TSH results were above their assay-specific upper reference limit in 10.7% of Roche results and 4.2% of Abbott results. Conclusion: Biochemical assessment of levothyroxine replacement may be dependent on the type of TSH assay. Laboratorians and clinicians should be aware that the lack of harmonisation between TSH methods and their assay-specific reference ranges may potentially lead to different patient management decisions. We suggest lot verification in laboratories should include processes to identify cumulative drift in assay performance.